Contribution of Health and Social Protection Expenditure to Human Development in Indonesia: Evidence from Sulawesi Region - Regina, Regina; Rabb, Ahmad Faqhruddin Abdur; Andriani, Shadry; Irwandi, Irwandi (International Journal of Economics and Management Research, 2025)
Fiscal policy is used to increase the HDI in Indonesia.Prioritizing human development and improving human resources should be supported by adequate regional spending allocation. Public spending of a social nature (health, education and social protection) contributes to the decline in the HDI which is sourced from socio-economic inequality.This study focuses on efforts to show empirical evidence of the relationship between health spending and social protection spending on the HDI level in the Sulawesi Region throughout 2018 to 2023. The Sulawesi Region is a concern for the central government in preparing the 2025-2029 RPJMN, where the issue of human development and improving the quality of human resources is still the main focus.The type of data in the study uses Sulawesi regional panel data consisting of 6 (six) provinces during 2018-2023. Model estimation uses the STATA 14 application. The results of the analysis show that Health spending (X1) has a positive and significant effect on the Human Development Index (Y) in the Sulawesi region. In addition, social protection spending does not have a significant effect on the Human Development Index (Y) in the Sulawesi region.